PSYCHOLOGICAL CAPITAL AS A MEDIATOR BETWEEN TRANSFORMATIONAL LEADERSHIP AND JOB STRESS: EMPIRICAL EVIDENCE FROM HEALTH SECTOR IN PAKISTAN (The Research of Medical Science Review, 2025)
This study aims to examine the relationship between perceived transformational leadership and job stress through psychological capital. Data were collected from 302 non-managerial employees at different hospitals in Pakistan through stratified random sampling in two stages. Hierarchical linear regression analysis and the bootstrapping method were utilized to quantify the mediation effect of psychological capital. The results demonstrate that perceived transformational leadership and job stress are negatively associated, perceived transformational leadership and psychological capital are positively associated, and psychological capital and job stress are negatively associated. Furthermore, findings also support the role of psychological capital as a partial mediator. Thus, the application of transformational leadership in organizations can automatically build up employees’ psychological capital, which, in turn, will mitigate job stress among employees. The implications and limitations of this study are discussed.